1983
DOI: 10.1016/0014-5793(83)80896-5
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of the N‐terminal domain of calf thymus histone H2A.Z

Abstract: The minor histone H2A subtype, H2A.Z, has been purified to homogeneity from calf thymus and subjected to automated Edman degradation. The sequence of the first 30 amino acids possesses only 60% homology with major H2A subtypes of the same tissue. This sequence difference is more extreme than that exhibited between evolutionarily distant major H2A subtypes. However, an analysis of secondary structure reveals that H2A.Z and major H2A subtypes exhibit the same general topographical features within their N‐termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…2). In addition, with long exposure a more slowly migrating, fainter band appeared; this band perhaps corresponds to an acetylated form of H2A.Z, an H2A variant with 5 N-terminal lysines (Ball et al, 1983) that is related to hvl.…”
Section: Binding Of Antipenta Antiserum To Ratmentioning
confidence: 99%
“…2). In addition, with long exposure a more slowly migrating, fainter band appeared; this band perhaps corresponds to an acetylated form of H2A.Z, an H2A variant with 5 N-terminal lysines (Ball et al, 1983) that is related to hvl.…”
Section: Binding Of Antipenta Antiserum To Ratmentioning
confidence: 99%
“…The initial residue of the histone H2A N termini of many organisms (10,38), including Tetrahymena (29,30), can be blocked by N-terminal acetylation, a conserved process that adds an acetyl group to the first amino acid of many histone and nonhistone proteins (57). Since Nterminal acetylation abolishes one positive charge at the major H2A N terminus, it affects the mobility of major H2A.1 in the mutant, and if this process occurs for some but not all H2A.1 molecules, it might account for the electrophoretic heterogeneity observed in the RRRRR mutation.…”
Section: Resultsmentioning
confidence: 99%
“…H2A.Z has been found in diverse organisms, including Tetrahymena (83), Saccharomyces cerevisiae (39,65), Schizosaccharomyces pombe (15), Drosophila (79), Arabidopsis thaliana (14), sea urchins (24), chickens (19,36), and mammals (10). Phylogenetic analysis of H2A protein sequences (73) demonstrated that the major H2As and the H2A.Z variants diverged early in eukaryotic evolution and that the H2A.Zs show even less evolutionary divergence than the major H2As.…”
mentioning
confidence: 99%
“…H2AFZ gene has been characterized in the human (Hatch and Bonner, 1988, 1990and 1995, mouse (Faast et al, 2001), cow (Ball et al, 1983), rat (NM_022674) and other species. Mice deficient in H2AFZ died early in development, i.e., around the time of implantation (Faast et al, 2001).…”
Section: Introductionmentioning
confidence: 99%